Experimental and Simulation Study on Gas Explosion in Confined Pipe - Siti Zubaidah, Sulaiman; R. M., Kasmani; A., Mustafa; Miss Hasimawaty, Mat Kiah (2015)
Experimental tests on hydrogen-enriched methane were simulated using numerical CFD tool FLACs. In this work, hydrogen concentration ranges between 4 to 8 % v/v was mixed with methane/air to observe the characteristic of flame speed and maximum pressure profile during the gas explosion. Experimental work was carried out in a closed pipe containing 90 degree bends with a volume of 0.41 m3 which operates at ambient conditions. From the experiment observation, adding hydrogen into methane-air mixture, the pressure is approximately 2 times higher and flame speed in a factor of 2 to 25 compared with pure methane-air gas explosion. Results also show that FLA Cs is under-predicted the flame speed and mass burning rate when low hydrogen concentration diffused in methane-air. This is due to low hydrogen content in methane-air mixture which limits the hydrogen diffusivity yet reducing the burning rate. It also observed that the presence of 90 degree bend in closed pipe system influences the explosion severity to the factor of 2-3 using simulation, as compared to the experimental done. There are significant discrepancies between experimental and simulation, however, the results seem conservative in general.